Indexes to Debates of the House of Assembly (Hansard) - South Africa Parliament, House of Assembly (Cape Town Government Printers, 1979)
South Africa Parliament House of Assembly. Debates of the House of Assembly (Hansard). Debates of Standing Committees.
Debates of the House of Assembly (Hansard). Debates of Standing Committees published annually and parallel with Afrikaans title. Merged with: Debates of the House of Delegates, and; Debates of the House of Representatives, to form: Debates of Parliament. 139 v. 22 cm.
Keywords: Indexes to Debates; House of Assembly; Hansard; Third Session; Sixth Parliament; 2 February; 22 June; 1979; Vol. 84; ISBN 0621059226; JC045379; Index to Questions; Standing Committee; House of Representatives; House of Delegates